2007
DOI: 10.1111/j.1600-0625.2007.00622.x
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal delivery of proteins mediated by non‐covalently associated arginine‐rich intracellular delivery peptides

Abstract: Plasma membranes of animal cells are generally impermeable to macromolecules. Protein transduction mediated by protein transduction domains (PTDs) covalently cross-linked to cargoes for cellular internalization has previously been demonstrated. Peptides with PTDs could be an effective way to deliver proteins into living cells or tissues in vitro. In this report, we demonstrate that arginine-rich intracellular delivery (AID) peptides are able to facilitate the delivery of proteins into animal cells and to penet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 37 publications
(72 reference statements)
2
60
0
Order By: Relevance
“…Hou et al (2007) found that some arginine-rich intracellular delivery (AID) peptides (TAT, R9, R9Z and SR9) could enhance the delivery of green fluorescent protein (GFP) in the animal skin without conjugation with the transported protein. The best permeation ability of the cargo protein and AID (SR9) mixture into cells was achieved with a ratio of 1:3.…”
Section: Non-conjugated Peptidesmentioning
confidence: 99%
“…Hou et al (2007) found that some arginine-rich intracellular delivery (AID) peptides (TAT, R9, R9Z and SR9) could enhance the delivery of green fluorescent protein (GFP) in the animal skin without conjugation with the transported protein. The best permeation ability of the cargo protein and AID (SR9) mixture into cells was achieved with a ratio of 1:3.…”
Section: Non-conjugated Peptidesmentioning
confidence: 99%
“…The cell-penetrating peptides interact with lipids in the SC, thus destabilizing the outermost layer of the skin and enhancing permeability. 117,118 Conjugation of Pep-1 peptides to TRS remarkably increased the delivery of liposomal drugs into human keratinocytes (HaCaT) when compared to Tr alone. 119 TXG-Pep1-Tr treatment significantly expedited recovery in skin barrier function when compared to animals treated with TXG aqueous solution.…”
Section: Preclinical Applications As Antiscarring Anti-atopic Dermatmentioning
confidence: 99%
“…Topical administration of several peptides would be attractive, including IGF-1, TGF-b, leptin, 14-3-3 proteins (for wound healing), interferon a (antiviral), cyclosporine (for treatment for autoimmune diseases), bacitracin (for skin infections), and palmitoylglycyl-histidyl-lysine tripeptide (for stimulation of collagen synthesis), among many others (39,(78)(79)(80)(81)(82)(83). In addition, several peptides have been applied to the skin and studied as antigens for the development of topical vaccines (84).…”
Section: Transdermal Delivery With Cppsmentioning
confidence: 99%